The Place of Peace in the ITER Machine Assembly Launch: Thematic Analysis of the Political Speeches in the World's Largest Science Diplomacy Experiment. - Carayannis, Elias G.; Draper, John (Peace & Conflict, 2021)
This study begins by reviewing the historical importance of peace in the ITER fusion experiment, the world's largest science diplomacy experiment, including by referencing other nuclear peacebuilding attempts, like the Baruch Plan and Atoms for Peace. It thematically analyses the speeches delivered by ITER consortium member state leaders at the July 28, 2020 ITER Machine Assembly Phase launch, which covered topics including fusion being a clean and safe form of energy and fusion's potential applications for climate management. The study emphasizes that Putin and the US representative did not reference peace, despite ITER being conceived by the Soviet Union and USA as a peacebuilding experiment, while China and others did. To address backsliding, the study recommends ITER engaging with the Call for a Global Commission for Urgent Action on Fusion Energy, issued in 2020, which incorporates a peacebuilding strand.